Contentious connective action: a new kind of life-political association for problematizing how expert systems operate. Issue 1 (2nd January 2019) - Bang, Henrik; Halupka, Max
ABSTRACT: Neoliberalism and populism both challenge the idea that democratic politics is of and by 'the people.' Neoliberalism suggests technocracy as the way ahead for nudging laypeople to do the right things. Populism appeals to the morality of an exceptional leader required for tumbling 'the system' and make the home of 'We the People' whole again. Both positions consider laypeople like clay to be formed in their own image. The logic of contentious connective action is a direct response to this political degradation of the layactor. Without laypeople being able chronically to problematize how things are done by expert systems, there can be no real democracy. Hence, it is about time we bring the lifeworld with its capable and knowledgeable laypeople back into the fold. Technological development has made it possible for the lifeworld to attain global and not just local significance. Its spontaneous activities in local time-space can now connect globally, enabling worldwide demonstrations in the name of 'we the 99%.'